The emergence of a market for football stars: Talent development and competitive balance in European football - Pehr-Johan Norbäck; Martin Olsson; Lars Persson (Research Institute of Industrial Economics (IFN), 2016)
We analyze how the Bosman ruling affected the market for star players and talent development in the European football market. We develop a model with sports competition and endogenous ownership of star players in which we show how the stiffer bidding competition over star players after the Bosman ruling has spurred talent development foremost in EU nations lacking established top clubs. This has a positive impact on their national teams' performance. However, the stiffer bidding competition has also lead to less competition in the Champions League, as non-established clubs prefer to sell their star players instead of challenging the top clubs. We provide empirical evidence consistent with these findings.
Keywords: J44; L50; L83; 330; Sports industry; star players; Champions League; Bosman ruling